MANAJEMEN ADMINISTRASI AKADEMIK KEPALA MADRASAH DI MTsN FILIAL SREBEGAN CEPER KLATEN TAHUN PELAJARAN 2016/2017 - Salam, Badrus (El-Hayah, 2018)
Abstract:This research aims at determining: 1) description of management of Principal academic administration at MTsN Filial Srebegan Ceper Klaten, 2) supporting and inhibiting factors solutions in implementing Principal academic administration at MTsN Filial Srebegan Ceper Klaten. This research used qualitative descriptive approach. Technique of collecting data used observation, interview and document. Subject of this research was the Principal, while informants were the vice chief of curriculum and the teachers. Technique of data validity applied triangulation of source. Technique of data analysis used interactive model covering data collection, data reduction and conclusionThe result of this research shows that: 1) management of principal academic administration at MTsN Filial Srebegan is systematically in continuing process, including four activities, planning, organizing, actuating, and controlling. 2) Supporting factors of management of principal academic administration are strongly commitment by the principal to have better implementation on management of principal academic administration, most of teachers and staffs are educational academician degree-holder, inadequate classrooms for teaching and learning activities and strategic school location. Meanwhile, inhibiting factors are lack of ability on IT and minimum facilities also inhibit this implementation. Solutions in facing those difficulties are improving ability on IT by course or private, and procurement of facilities, such as library room, administrative room and additional facilities of IT, especially in teacher’s office and staff’s office, are needed.Keywords: Management, Academic administration, Principal